2022
DOI: 10.1111/petr.14239
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation in infants is associated with significant morbidity and mortality

Abstract: Background: Infants are subjected to hematopoietic stem cell transplantation (HSCT) due to malignant and non-malignant diseases. However, specific data concerning the outcome and transplantation-related complications in infants, as a separate age group, are limited. Our aim was to evaluate the impact of infancy on the outcome, toxicity, and complications after HSCT. Methods:We retrospectively analyzed data of 55 infants that underwent HSCT in our unit from May 1997 until February 2020, emphasizing on the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Oikonomopoulou et al 7 have recently reported 36% mortality in infants who received allo-HCT for the treatment of malignant or nonmalignant disease. Among 14 deaths in 39 patients with nonmalignant disease, eight (57%) occurred as the early death less than 100 days post transplant, and 12 (86%) were from treatment-related mortality.…”
Section: Ric-hct Is Preferred For Scid a Retrospective Study On 17 Pa...mentioning
confidence: 99%
“…Oikonomopoulou et al 7 have recently reported 36% mortality in infants who received allo-HCT for the treatment of malignant or nonmalignant disease. Among 14 deaths in 39 patients with nonmalignant disease, eight (57%) occurred as the early death less than 100 days post transplant, and 12 (86%) were from treatment-related mortality.…”
Section: Ric-hct Is Preferred For Scid a Retrospective Study On 17 Pa...mentioning
confidence: 99%